On Classical Adaptive Logics of Induction - Batens, Diderik; Haesaert, Lieven (Logique et Analyse, 2001)
This paper concerns the inference of inductive generalizations and of predictions derived from them. It improves on the adaptive logic of induction from On a Logic of Induction (Batens, Logic and Philosophy of Science, IV, 1, 2006, pp. 3-32) by presenting logics that are formulated strictly according to the usual adaptive standards. It moreover extends that paper with respect to background knowledge. We present logics that handle inductive generalizations as well as logics that handle prioritized background knowledge of three kinds: background generalizations, pragmatic background generalizations (the instances of which may be invoked even after the generalizations are falsified), and background theories. All logics may be combined into a single system.